PENGEMBANGAN MODUL BAHASA DAN SASTRA INDONESIA DI SMK KELAS X DENGAN MODEL KOOPERATIF TIPE STAD - Tsalitsatul Maulidah (MEDIA DIDAKTIKA, 2018)
The purpose of this study is (1) to describe the process of developing the Indonesian Language and Literature module in STAD type cooperative learning. (2) describe the quality of development of the Indonesian Language and Literature module in STAD type cooperative learning. This study uses the development method (Research and Development). The results of this study show student learning outcomes obtained as follows: Module valid with the percentage of linguists 95.0%, learning experts 95.0% and material experts 82.4% and practitioners with a percentage of 86.7%. In addition, to measure the effectiveness of the module can also be seen based on the achievement scores of student learning which shows an average of above 75, with a percentage of 100% for the test of implementation I and 98.0% of students in the test of implementation II. This research can be concluded that the module development process is carried out in several stages, and each stage faces a problem that must be solved. Module quality can be measured on the level of validity, practicality, and effectiveness. Modules are said to be effective, because based on the score of achievement of individual learning outcomes students get a score above 75 and the completeness of the class is above 75%, so, the development of the Indonesian language module with the Cooperative Model type STAD.